2013
DOI: 10.1002/jcp.24436
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt/β‐Catenin Signaling Promotes Engraftment of Mesenchymal Stem Cells to Repair Lung Injury

Abstract: We sought to explore the treatment effects and the repair mechanisms of bone marrow derived mesenchymal stem cells (MSCs) during HCl-induced acute lung injury (ALI). MSCs were delivered through the tail veins of rats 24 h after intranasal instillation of HCl. The results showed that MSCs did not ameliorate the histopathologic changes of ALI and pulmonary fibrosis. We found that the activated Wnt/β-catenin signaling may regulate the differentiation of MSCs and is associated with lung fibroblasts activation, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Upon stimulation by Wnt ligands, b-catenin is stabilized and then translocates to the nucleus, where it binds to T-cell factor/lymphoid enhancer factor (TCF/LEF) transcription factors, activating the expression of Wnt target genes, promoting cell proliferation (15)(16)(17) and limiting cell differentiation (16,18), thus contributing to both airway (18,19) and alveolar epithelial repair (20)(21)(22) after injury. Consistent with this concept, activation of b-catenin signaling by lithium chloride attenuated elastase-induced experimental emphysema (21), suggesting that b-catenin signaling contributes to lung repair/regeneration in response to various injuries.…”
Section: Fam13amentioning
confidence: 99%
“…Upon stimulation by Wnt ligands, b-catenin is stabilized and then translocates to the nucleus, where it binds to T-cell factor/lymphoid enhancer factor (TCF/LEF) transcription factors, activating the expression of Wnt target genes, promoting cell proliferation (15)(16)(17) and limiting cell differentiation (16,18), thus contributing to both airway (18,19) and alveolar epithelial repair (20)(21)(22) after injury. Consistent with this concept, activation of b-catenin signaling by lithium chloride attenuated elastase-induced experimental emphysema (21), suggesting that b-catenin signaling contributes to lung repair/regeneration in response to various injuries.…”
Section: Fam13amentioning
confidence: 99%
“…XAV939 could significantly suppress Wnt/␤-catenin signaling and promote the epithelial differentiation but had little impact on ATII cells. Previous reports suggested that when the Wnt/ ␤-catenin signaling is activated, BM-MSCs can differentiate into fibroblasts or myofibroblasts, and this process can be inhibited by DKK-1 (34). These findings prompted us to propose that inhibition of Wnt/␤-catenin signaling could promote the alveolar epithelial cell-mediated differentiation of autologous BM-MSCs into epithelial cells in the damaged lung, and hence the improvement in lung function.…”
Section: Discussionmentioning
confidence: 96%
“…Mesenchymal stem cells did not abrogate the histopathologic changes of HCl-induced acute lung injury and pulmonary fibrosis. We have previously shown that inhibition of Wnt/␤-catenin signaling by DKK-1, a natural inhibitor of the Wnt/␤-catenin signaling pathway, can promote the differentiation of exogenous BM-MSCs into epithelial cells in vivo and thus regulate lung injury and repair, although only a fraction of the exogenous cells are recruited (34). In addition, recruitment of endogenous mesenchymal stem cells to the injured lung is also observed (40).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Wang and coworkers, along with prior publications from this group and others (6,11,13), makes clear that the Wnt/␤-catenin signaling pathway plays a major role in pulmonary fibrosis. This pathway appears to affect two key cell types involved in lung injury and repair: it activates fibroblast proliferation and inhibits mesenchymal stem cell differentiation into epithelia (instead promoting differentiation into a fibroblast-like phenotype).…”
mentioning
confidence: 98%